Land use biodiversity impacts embodied in international food trade. (May 2016) - Chaudhary, Abhishek; Kastner, Thomas
Highlights: We calculate regional and global extinctions per ton for 170 crops in 184 countries. We estimate species loss embodied in global food trade for four vertebrate taxa. 17% of global biodiversity loss occurs due to commodities destined for exports. The region from where crop are sourced is more important than area imported. Imports of industrialized nations drive extinctions in tropical, biodiverse nations. Abstract: Agricultural land use to meet the demands of a growing population, changing diets, lifestyles and biofuel production is a significant driver of biodiversity loss. Globally applicable methods are needed to assess biodiversity impacts hidden in internationally traded food items. We used the countryside species area relationship (SAR) model to estimate the mammals, birds, amphibians and reptiles species lost (i.e. species 'committed to extinction') due to agricultural land use within each of the 804 terrestrial ecoregion. These species lost estimates were combined with high spatial resolution global maps of crop yields to calculate species lost per ton for 170 crops in 184 countries. Finally, the impacts per ton were linked with the bilateral trade data of crop products between producing and consuming countries from FAO, to calculate the land use biodiversity impacts embodied in international crop trade and consumption. We found that 83% of total species loss is incurred due to agriculture land use devoted for domestic consumption whereas 17% is due to export production. Exports from Indonesia to USA and China embody highest impacts (20 species lost at the regional level each). In general, industrialized countries with high per capita GDP tend to be major net importers of biodiversity impacts from developing tropical countries. Results show that embodied land area is not a good proxy for embodied biodiversity impacts in trade flows, as crops occupying little global area such as sugarcane, palm oil, rubber and coffee have disproportionately high biodiversity impacts.